Emotional Intelligence as a Predictor of Success in Online Learning - Berenson, Robin; Boyles, Gary; Weaver, Ann (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
As students increasingly opt for online classes, it becomes more important for administrators to predict levels of potential academic success. This study examined the intrinsic factors of emotional intelligence (EI) and personality to determine the extent to which they predict grade point average (GPA), a measure of academic success, among students attending community college. Stepwise multiple regression revealed that EI emerged as the most significant direct predictor of GPA. The addition of personality to EI significantly increased the amount of variance accounted for in GPA. Main conclusions are that soft skills are pertinent to academic success and may constitute a useful profile of the successful online student that could be applied to marketing, advisement, quality assessment, and retention efforts.